2014
DOI: 10.1039/c4nr03334e
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional layered semiconductor/graphene heterostructures for solar photovoltaic applications

Abstract: Schottky barriers formed by graphene (monolayer, bilayer, and multilayer) on 2D layered semiconductor tungsten disulfide (WS2) nanosheets are explored for solar energy harvesting. The characteristics of the graphene-WS2 Schottky junction vary significantly with the number of graphene layers on WS2, resulting in differences in solar cell performance. Compared with monolayer or stacked bilayer graphene, multilayer graphene helps in achieving improved solar cell performance due to superior electrical conductivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(65 citation statements)
references
References 43 publications
1
64
0
Order By: Relevance
“…SHG measurement has become an efficient way to characterize the structure, symmetry, and electronic and optical properties of materials. [98,99] For example, a graphene monolayer with inversion symmetry has no SHG response, i.e., the χ (2) is equal to zero. [100][101][102] The TMD odd layers have a strong SHG due to the absence of inversion symmetry while the SHG of the TMD with even layers is removed due to the inversion symmetry.…”
Section: Shgmentioning
confidence: 99%
See 2 more Smart Citations
“…SHG measurement has become an efficient way to characterize the structure, symmetry, and electronic and optical properties of materials. [98,99] For example, a graphene monolayer with inversion symmetry has no SHG response, i.e., the χ (2) is equal to zero. [100][101][102] The TMD odd layers have a strong SHG due to the absence of inversion symmetry while the SHG of the TMD with even layers is removed due to the inversion symmetry.…”
Section: Shgmentioning
confidence: 99%
“…It is clear that the value of the I p /I s ratio of the Janus MoSSe monolayer varies with incident angle, but there is no change for the alloyed MoSSe monolayer, confirming the existence of an out-of-plane dipole in Janus structures. [30] The out-of-plane and in-plane second-order susceptibility ratio χ (2) xxz /χ (2) yzz for the five Janus and alloyed MoSSe samples is shown in Figure 6e. A Janus structure has a χ (2) xxz /χ (2) yzz ratio of ≈10:1, further demonstrating the presence of an out-of-plane dipole.…”
Section: Shgmentioning
confidence: 99%
See 1 more Smart Citation
“…[131,147,[149][150][151][152] Shanmugam et al have studied the performance of Schottky barrier solar cells formed by growing graphene layers on WS 2 nanosheets. [135] The photoelectric conversion efficiency of multilayer, bilayer, and monolayer graphene stacked on the WS 2 monolayer can reach 3.3%, 2.9%, and 2.3%, respectively. The power conversion efficiency for WSe 2 /MoS 2 vdWH on Si/SiO 2 substrate is ≈0.2%, and the external quantum efficiency is ≈1.5%, as reported by Furchi et al [136] Gong et al have reported that the power conversion efficiency of the WS 2 /MoSe 2 vdWH prepared through a two-step CVD method is ≈0.12% without any external gates.…”
Section: /Insulatormentioning
confidence: 99%
“…Shanmugam et al [135] WSe 2 /MoS 2 MX 2 /semiconductor Power conversion efficiency ≈ 0.2% External quantum efficiency ≈1.5%…”
Section: Devicementioning
confidence: 99%